ANALYSIS OF THE EFFECTIVENESS OF REGIONAL FINANCIAL BUDGETING THAT SUPPORTS THE FULFILLMENT OF THE RIGHTS OF PERSONS WITH DISABILITIES IN MAGELANG REGENCY - Listiani, Alita Firda; Bharata, Risma Wira (Transpublika Publisher, 2022)
Persons with disabilities are included in the group with Social Welfare Problems (PMKS). Article 26 of the Draft Law on Persons with Disabilities explains that both the central government and local governments have an obligation to carry out planning, respect, protect, and fulfill the rights of persons with disabilities. In this regard, it is necessary to coordinate from the central level to the regional level for the realization of the use of the budget in carrying out various rights fulfillment, respect and protection for persons with disabilities. This study aims to determine the level of effectiveness calculated from the comparison of the total budget and its realization for persons with disabilities in Magelang Regency. This research is quantitative research by adopting descriptive method. The results of the calculation on the effectiveness analysis show a figure of 100% in 2021 and 55.1% in the period January-June 2022 which means that the total budget and its realization have met the effective results for persons with disabilities in Magelang Regency.